Response of the photosynthetic characteristics and antioxidant system of Suaeda salsa to the changes of underground brine depth - Wang, Ping; Xu, Wenjing; Zhang, Zehao; Fu, Zhanyong; Li, Tian; Sun, Jingkuan (Frontiers in Plant Science, 2024)
Water and salt conditions are key factors influencing vegetation growth on shell island in the Yellow River Delta. The laboratory simulation experiment was carried out to investigate the effect of the changes of underground brine depth on Suaeda salsa using four levels of groundwater: 0 cm, 15 cm, 30 cm and 45 cm. The results showed that different underground brine depths had significant impacts on the photosynthetic characteristics and antioxidant system of S. salsa, and 0-30 cm underground brine depth was suitable for S. salsa growth. The net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), light utilization efficiency (LUE) and carboxylation efficiency (CE) of S. salsa increased first and then decreased with increasing depth of underground brine. The stomatal limitation value (Ls) and WUE of S. salsa reached the peak value at the groundwater depth of 0 cm, and water use efficiency was reduced by 19.4%, 8.0% and 8.6% at 15 cm, 30 cm, and 45 cm, respectively, compared to the 0 cm treatment. With the deepening of underground brine depth, the value of LUE and CE firstly increased and then decreased, and reached the peak value when the depth was 30 cm. The antioxidant enzyme (SOD, POD and CAT) activities of S. salsa decreased and then increased with the increase of underground brine depth. The enzyme activities were the lowest when the underground brine depth was 30 cm. As the groundwater depth increased, MDA content decreased and then increased. The highest degree of membrane peroxidation in S. salsa leaves was observed at the depth of 45 cm. Our study reveals that the antioxidant capacity of S. salsa was weakened at the underground brine depth of 45 cm and the growth of S. salsa was inhibited.